1981
DOI: 10.1007/bf00632980
|View full text |Cite
|
Sign up to set email alerts
|

Pigmented villonodular synovitis with bone involvement

Abstract: Pigmented villonodular synovitis with bone involvements have been reported at various sites. The mode of bone involvement is still controversial. In the present report, out of 47 cases of pigmented villonodular synovitis there were six osseous involvements (at ankle, wrist, elbow, scapula, hip and knee) with bizarre manifestations. The lesions at ankle, wrist and elbow were peculiar, mimicking neoplasm. All cases were treated by operative methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
32
2
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 16 publications
4
32
2
3
Order By: Relevance
“…A literature review identified only 24 documented cases of PVNS involving the elbow joint; of these, 15 were case reports and nine were included in seven large retrospective PVNS series of all sites: one case from Scott (8), one from Granowitz et al (2), two from Docken (5), one from Pandey and Pandey (15), one from Miller (14), one from Ushijima et al (11) and two from Schwartz et al (4) (Table I). In the seven large retrospective PVNS series, LPVNS comprised 246 and DPVNS comprised 78 of the 421 cases.…”
Section: Discussionmentioning
confidence: 99%
“…A literature review identified only 24 documented cases of PVNS involving the elbow joint; of these, 15 were case reports and nine were included in seven large retrospective PVNS series of all sites: one case from Scott (8), one from Granowitz et al (2), two from Docken (5), one from Pandey and Pandey (15), one from Miller (14), one from Ushijima et al (11) and two from Schwartz et al (4) (Table I). In the seven large retrospective PVNS series, LPVNS comprised 246 and DPVNS comprised 78 of the 421 cases.…”
Section: Discussionmentioning
confidence: 99%
“…The first reported case of PVNS of the ankle was [7]. Since then there have been a few hundred cases of PVNS of the ankle reported in the literature [4,11] but in only 9 of 15 cases of PVNS occurring in children (Table 1). PVNS usually affects adults during their third or fourth decade in life [10].…”
Section: Discussionmentioning
confidence: 99%
“…Surgical treatment should be performed as soon as possible in order to prevent cartilage infiltration which can occur [11,16].…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Bony structures of the knee joint can be affected by PVNS. [5][6][7][8] There is no known causal link between total knee arthroplasty (TKA) and PVNS. There also is no known relationship between PVNS and implant loosening after TKA in the literature.…”
mentioning
confidence: 99%
“…Bone involvement by PVNS has been reported by many investigators. [5][6][7][8] The features of bone involvement by PVNS may be variable, from cystic to osteolytic lesions similar to a tumor. 4,5 Patients who have diffuse PVNS may have destructive changes in the knee joint, including periarticular cysts, erosions, and joint space narrowing.…”
mentioning
confidence: 99%